Relayout Tempat Penyimpanan Suku Cadang Motor Menggunakan Metode Class Based Storage untuk Efisiensi Waktu Pencarian - Bahrudin, Moch Arif; Herlina, Herlina (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
This study aims to enhance the operational efficiency of Toby Motor Workshop through the implementation of the Class-Based Storage (CBS) method in the relayout of spare parts storage. The workshop faces challenges such as disorganized warehouse layouts, difficulties in locating items, and lengthy spare parts retrieval times. To address these issues, data on 223 types of spare parts were collected, including usage frequency and retrieval times over a 12-week period. The ABC classification method was employed to group spare parts into three categories—A, B, and C—based on usage frequency and item value. Class A items, with high usage frequency, were placed in more accessible locations. The findings indicate that applying the CBS method significantly reduced retrieval times, optimized space utilization, and streamlined warehouse workflows. The proposed warehouse layout also improved inventory management efficiency and reduced staff travel distances when retrieving items. The implementation of CBS not only boosts operational efficiency but also supports a more structured warehouse management system. Consequently, this study provides practical contributions to improving productivity and competitiveness at Toby Motor Workshop. Keywords: Class Based Storage, Klasifikasi ABC, Relayout